Endothelial GABBR2 Regulates Post-ischemic Angiogenesis by Inhibiting the Glycolysis Pathway - Zhang, Hongze; Zhou, Hong; Yuan, Jianying; Nan, Yong; Liu, Jingquan (Frontiers in Cardiovascular Medicine, 2021)
Purpose: Angiogenesis post-ischemia plays an essential role in preventing tissue from ischemic damage by improving the blood recovery. To determine the regulatory mechanism of ischemic angiogenesis therefore could provide effective therapeutics for ischemic injury. Materials and methods: The RNA-seq database was used to predict the association of gamma-aminobutyric acid type B receptor subunit 2 (GABBR2) with endothelial specific expression. The role of GABBR2 in angiogenesis was verified in vitro by downregulating GABBR2 in HUVECs with lentiviral vectors. Besides, the in vivo effect of GABBR2 on blood recovery of ischemic hindlimb was demonstrated by establishing hindlimb ischemia model in normal and GABBR2 adenoviral vectors infected mice. Then the mobilization of endothelial progenitor cells (EPCs) in peripheral blood post-ischemia was determined by flow cytometry. Finally, the XF analyzer and western blot were used to determine the effect of GABBR2 on endothelial metabolism. Results: The RNA-seq result indicated a strongly association between GABBR2 and endothelial revascularization, and the upregulation of GABBR2 was detected in both hypoxia treated HUVECs and ischemic mice hindlimb. Hypoxia treatment for 6 hours increased proliferation, migration and tube-formation of HUVECs, which were inhibited by GABBR2 knockdown (KD). Additionally, GABBR2 downregulation significantly decreased the blood flow recovery of mice ischemic hindlimb. The expression of EPCs markers CD34+ and CD133+ significantly decreased in the peripheral blood post hindlimb ischemia. Mechanically, glycolysis dominated metabolism of HUVECs was compromised by GABBR2 knockdown. Evidences in decreased expression of HKII, PFKFB3 and PKM1 also supported the compromised glycolysis induced by GABBR2 downregulation. Conclusion: Our study demonstrated that GABBR2 regulated angiogenesis post-ischemia by inhibiting glycolysis pathway.